Methodology to increase oil reserves by identifying optimal time to abandon non-economic wells - Sandoval, Publio-Alejandro; Fernández, Fabián-Ricardo; Ordoñez-Rodríguez, Aníbal; Rincón-Bonilla, Claudia; Jerez, Leydy-Johana (CT&F - Ciencia, Tecnología y Futuro, 2011)
Estimating reserves is one of the most important tasks in the oil industry. It is the process that determines the recoverable oil in a field, area or region. However, incorporating the production of a well beyond its economic limit has the effect of loss of value, because it forces economically good wells to sustain those that are not. A corporate vision of the topic, calls for greater attention to strategies to select wells for abandonment, as an important variable in the planning of production scenarios and estimating reserves. The purpose of this paper is to describe the methodology used to obtain higher value in reserves calculated for a given asset, by analyzing direct production costs and the design of an optimum well abandonment timetable. The methodology can be applied in all the fields in which an analysis of this type has not been considered, which run the risk of having incorporated in their reserve estimate a number of wells in which the economic balance is negative, thus affecting the performance of the reservoir's better wells. Additionally, it includes a case application of the methodology involving a field in a Colombian basin. The results show a 5 year extension in economic limit, with a significant increase in the amount of the asset's recoverable reserves.